The openness of the enclosed convent. Evidence from the Lüne Letter Collection - Wareham, E (ICI Berlin Press, 2022)
This article draws on the nearly 1800 letters which survive from the Benedictine convent of Lüne, near Lüneburg in northern Germany, and were written between c. 1460 and 1555. It explores the textual and visual strategies which nuns in the later Middle Ages used to negotiate their enclosed status. It suggests that the language and imagery of openness were a means for the nuns to remind those outside the convent wall of their presence and purpose in life.